Case report: Single patellar metastasis of breast cancer - Ma, Xuefeng; Yan, Yunyu; Cai, Pengli; Liu, Ying; Zhang, Ranxu; Dong, Yanhong; Liu, Song; Li, Junfei; Zhao, Jian; Zhang, Ping (Frontiers in Endocrinology, 2025)
Breast cancer is recognized as the most prevalent malignant tumor among women and is prone to distant metastasis. However, patella metastasis in breast cancer cases is very rare. This case report presents the case of a 63-year-old Chinese female patient who experienced right knee pain and discomfort. The patient had a prior history of right breast tumor resection, and was diagnosed with single patellar metastasis of breast cancer.